The last oracle : a novel - Rollins, James, 1961- (New York : Morrow Avon, 2008)
An ancient relic, a murdered man, an international think tank of scientists known as the Jasons who have discovered a way to bioengineer autistic children, and a plot to wipe out a quarter of the world's population have two men racing against time to solve a mystery that dates back to the first famous oracle of history--the Greek Oracle of Delphi.
Keywords: Bioterrorism -- Fiction; Suspense fiction; Science fiction